Pengembangan Sistem Seleksi Proposal Penelitian Berbasis Web Service Menggunakan REST API - Daru Prasetyawan; Prihanto Dwi Rahmanto (Jurnal Teknologi Informasi dan Multimedia, 2024)
Web service-based application development has become a vital component of the modern in-formation technology ecosystem. The implementation of web services facilitates interoperability among diverse systems and platforms. REST API (REpresentational State Transfer Application Programming Interface) is one of the most popular architectures for creating efficient and scalable web services. This study examines the implementation of REST API in the development of web service-based applications. The case study focuses on the creation of a Web service-based Research Proposal Selection System. The REST API implementation method in this study adheres to the system development life cycle (SDLC) to ensure that the developed API meets business needs while being efficient, secure, and reliable. The analysis phase is conducted to gather both functional and non-functional REST API requirements. During the design phase, the REST API architecture is designed in detail, including how data will be transferred and processed, and how the API will interact with databases and other systems. Furthermore, in the implementation phase, the REST API is developed, ensuring that each endpoint operates correctly. In developing the Proposal Selection System, the implementation of web services integrates data from various existing sys-tems, including employee, academic, and research data. The system encompasses various features, such as proposal import, proposal mapping, proposal review, proposal assessment, proposal se-lection, and reporting. The research findings indicate that implementing the REST API simplifies the development of web service applications. The test results reveal that the average response time is relatively stable, measuring 31 ms without iterations and 29 ms with five iterations.